CURRENT INCIDENCE OF ANTIBIOTIC RESISTANT BACTERIA OF UROLOGIC BACTERIA FROM PATIENTS WITH URINARY TRACT INFECTION AT A HEALTHCARE FACILITY IN SOUTHWEST NIGERIA. - Ajayi, Ayodele Oluwaseun; Akoledowo, Opeyemi Sarah; Adegbite, Adedoyin Comfort; Ogunduboye, Ezekiel Busayo; Yakub, O. Z.; Balogun, O. A. (FUDMA Journal of Sciences, 2025)
Uropathogenic bacteria are known to be significant pathogens responsible for urinary tract infections (UTIs). UTIs are among the most prevalent infectious diseases, affecting millions of people worldwide, and are a significant healthcare burden. The study determined the antibiotic susceptibility patterns of uropathogenic bacterial isolates obtained from UTIs at a study location in Ekiti-State, Nigeria. Fifty Gram-negative (8 E. coli, 25 K. pneumoniae and 17 P. aeruginosa) and 6 Gram-positive (6 S. aureus) bacterial isolates were obtained from patients referred to the laboratory. Each isolate was identified accordingly using conventional biochemical test. All bacteria recovered were subjected to antibiotic susceptibility tests using the agar disk diffusion method. The bacteria were further tested presumptively for the formation of biofilms. All the Gram-negative bacteria were resistant to ceftazidime 50(100.0%). Furthermore, the Gram-negative bacteria showed the least resistance to chloramphenicol 17(34%) and ciprofloxine 23(46%). All the S. aureus strains showed elevated resistance against the antibiotics tested. Thirty five multiple antibiotic resistance patterns were observed among the isolates and the most prominent patterns were observed as Crx-Van-Ctr-Ctx-Cpz-Tet-Gen-Mem-Cot-Amk, Crx-Van-Ctr-Ctx-Cpz-Tet-Cot-Gen-Mem-Cip-Amk and Crx-Van-Chl-Ctr-Ctx-Cpz-Tet-Cot-Gen-Mem-Cip-Amk. The research has shown that multidrug resistant bacteria in UTI is a serious healthcare problem and efforts must be made to enforce strict antibiotic treatment regimen to prevent the emergence and spread of antibiotic resistant bacteria in clinical settings.
Keywords: Antibiotic; Multidrug resistance; Antibiotic resistance; Uropathogens